Pro-inflammatory Stimulation of Monocytes by ANCA Is Linked to Changes in Cellular Metabolism - O'Brien, Eóin C.; White, Carla A.; Wyse, Jason; Leacy, Emma; Porter, Richard K.; Little, Mark A.; Hickey, Fionnuala B. (Frontiers in Medicine, 2020)
Clinical and experimental data suggest that pathogenesis in anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis is driven by ANCA-mediated activation of neutrophils and monocytes. While the role of neutrophils has been extensively investigated, the function of monocytes remains relatively understudied. We have previously demonstrated that stimulation of monocytes with anti-myeloperoxidase (MPO), but not anti-proteinase-3 (PR3), antibodies results in production of the pro-inflammatory cytokine IL-1β. Changes in cellular metabolism, particularly a switch to glycolysis, have recently been linked to activation of immune cells and production of IL-1β. Therefore, we investigated the metabolic profile of monocytes following ANCA stimulation. We found a significant increase in glucose uptake in anti-MPO stimulated monocytes. Interestingly, both anti-MPO and anti-PR3 stimulation resulted in an immediate increase in glycolysis, measured by Seahorse extracellular flux analysis. However, this increase in glycolysis was sustained (for up to 4 hours) in anti-MPO- but not anti-PR3-treated cells. In addition, only anti-MPO-treated cells exhibited increased oxidative phosphorylation, a metabolic response that correlated with IL-1β production. These data indicate that monocyte metabolism is altered by ANCA, with divergent responses to anti-MPO and anti-PR3 antibodies. These metabolic changes may underlie pathologic immune activation in ANCA associated vasculitis, as well as potentially contributing to the differing clinical phenotype between PR3- and MPO-ANCA positive patients. These metabolic pathways may therefore be potential targets for therapeutic intervention.